Clinical Value of Assessing Cytokine Levels for the Differential Diagnosis of Bacterial Meningitis in a Pediatric Population. Issue 13 (March 2016) - Ye, Qing; Shao, Wen-Xia; Shang, Shi-Qiang; Shen, Hong-Qiang; Chen, Xue-Jun; Tang, Yong-Min; Yu, Yong-Lin; Mao, Jian-Hua
Abstract : Abstract: We performed a prospective observational study to evaluate the utility of measuring inflammatory cytokine levels to discriminate bacterial meningitis from similar common pediatric diseases. Inflammatory cytokine levels and other cerebrospinal fluid (CSF) physicochemical indicators were evaluated in 140 patients who were diagnosed with bacterial meningitis via microbiological culture or PCR assay. The CSF concentrations of interleukin (IL)-6 and IL-10, CSF/blood IL-6 and IL-10 ratios, CSF white blood cell count, and CSF micro total protein were significantly elevated in bacterial meningitis patients compared with healthy children or patients with viral encephalitis, epilepsy, or febrile convulsions ( P < 0.001). The area under the curve values for CSF concentrations of IL-6 and IL-10, CSF/blood IL-6 and IL-10 ratios, CSF white blood cell count, and CSF micro total protein to identify bacterial meningitis episodes by receiver-operating characteristic analysis were 0.988, 0.949, 0.995, 0.924, 0.945, and 0.928, respectively. The area under the curve for the combination of CSF IL-6 and CSF/blood IL-6 ratio was larger than that for either parameter alone, and the combination exhibited enhanced specificity and positive predictive value. After effective meningitis treatment, CSF IL-6 levels dropped significantly. These results suggest that CSF IL-6 and CSF/blood IL-6 ratio are good biomarkers in discriminating bacterial meningitis. Evaluating CSF IL-6 and CSF/blood IL-6 ratio in combination can improve diagnostic efficiency. Additionally, CSF IL-6 levels can be used to monitor the effects of bacterial meningitis treatment.